RELEVANSI PALPASI DALAM PEMERIKSAAN RADIOGRAFI: Relevance of Palpation in Radiographic Examination - Sukandar Avianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2019)
In abdomen, kidney ureter blader, Vertebrae Lumbo Sacral and sacrum radiographexamination the technicians must determine organ border for determine center pointall radiograph examination, and for sure that border are correct place, the radiographer must doing palpation on the organ which is determined, the palpationmust doing because some organ which is determined are covered by the patient’s clothes when patient’s change their examination clotches, some palpation activitycarried out by the radiographer very likely subject to legal provisions by article 335Indonesian criminal law about the actions of others is not pleasant, especially if theradiographer does not have an operational standard procedure about palpation indoing radiograph examination. Researcher use qualitative research method with theaim of explaining how to make boundaries in radiographic examination withoutpalpation and conduct a review of the relevance of palpation activities in radiologicalexaminations.The result of the study show the way radiographers carry outradiographic examination without palpating namely by verbal means, where the radiographers asks the patient with good and polite words to show and suppress thebody part that radiographer wants to be pointed or pressed by the patient’s fingerthemselves and the relevance of the palpation activity can not be left to noncooperative patients or patients who do not be aware of. For cooperative patientspalpation activity should be clearly written in the standard radiographic examinationprocedure.